Integrating service-learning and consulting in distance education - Germain, Marie-Line (Bingley, U.K. : Emerald Publishing Limited, 2019)
The pressures upon students from employers are greater than ever. Demands for a highly skilled workforce in a digitalized economy mean that higher education institutions need to do more to prepare their student bodies for this new way of working. The geographical boundaries set by traditional on-campus courses prevent most universities from allowing online students to engage in community service. Online service-learning responds to this limitation by initiating the transfer of in-person community service to the online environment. E-service learning addresses the growing demand for flexible online courses and programs.Anchored in research and supported by eight years of successful implantation, this book presents an award-winning e-service-learning model which allows students to enhance their employability with real work experience. Faculty can go beyond theory while building their service requirements, and may use e-service-learning to offer real world applications and hands-on experience. Clients benefit from pro bono services, and universities are able to fulfill their strategic goals, serve the community-at-large, and grow their online programs by offering students a unique online course experience. This book advocates a model and instructions for faculty to successfully integrate a remote service-learning and consulting component in an online course making this an illuminating text for higher education researchers and leaders alike.
Prelims -- Introduction -- Theoretical underpinnings -- Application: integration of e-service-learning -- Recommendations for success -- Conclusion -- References -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Web-based instruction; Distance education; Education -- Higher; Educational strategies & policy